2005
DOI: 10.1002/chin.200523256
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid‐β as a “Difficult Sequence” in Solid Phase Peptide Synthesis

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…Complementary techniques such as SDS-PAGE, size exclusion chromatography, and/or dynamic light scattering (DLS) also report on the quality of the starting material. While 95% purity is the minimal acceptable level, common contaminants rise from truncated sequences (peptides missing one or more amino acids) [53][54][55], amino acid racemization, side reactions during the peptide cleavage, and deprotection and oxidation of amino acids (in particular methionine (Met)), which occur during the synthesis. Met oxidation can be minimized with proper synthesis methodology [55,56]).…”
Section: Purity Of Peptidesmentioning
confidence: 99%
“…Complementary techniques such as SDS-PAGE, size exclusion chromatography, and/or dynamic light scattering (DLS) also report on the quality of the starting material. While 95% purity is the minimal acceptable level, common contaminants rise from truncated sequences (peptides missing one or more amino acids) [53][54][55], amino acid racemization, side reactions during the peptide cleavage, and deprotection and oxidation of amino acids (in particular methionine (Met)), which occur during the synthesis. Met oxidation can be minimized with proper synthesis methodology [55,56]).…”
Section: Purity Of Peptidesmentioning
confidence: 99%
“…Synthesis of the human β-amyloid (1-42) peptide (H-DAEFRHDSGYEVHHQKLVFFAEDVGSNKGAIIGLMV-GGVVIA-OH) by conventional SPPS has been reported to be difficult owing to the high hydrophobicity of the C-terminal segment and on-resin aggregation [18,19]. We initially synthesized β-amyloid 1 -42 with deprotection times of 15 min × 1, acylation times of 35 min, and capping times of 5 min for a total synthesis time of 47.8 h. β-Amyloid 1 -42 was then synthesized with 1 min × 2 deprotection 5 min acylation times, and 2.5 min × 2 capping times giving a total synthesis time of 14 h and produced a crude peptide with similar purity to the long synthesis.…”
Section: β-Amyloid (1-42)mentioning
confidence: 99%
“…Several spectroscopic studies have indicated that the copper-binding site of Aβ consists of the three histidine residues His6, His13 and His14 and an as yet undefined fourth ligand; proposed ligands include Tyr10 [19,[38][39][40], the Nterminal nitrogen [30] or an as yet unidentified carboxylate side chain [31,32].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%